Pengawasan Pemerintah Daerah dalam Pengawasan Tambang Galian Batuan di Kecaamatan Bontotiro Kabupaten Bulukumba - Aldiani Fitriayu Sam (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2023)
Rock quarry mining activities constitute one of the sectors contributing to regional economic development. However, if not properly supervised, such activities may generate various legal, social, and environmental problems. Therefore, government supervision plays a crucial role in ensuring that mining operations comply with applicable laws and regulations. This study aims to analyze government supervision of rock quarry mining activities in Bontotiro District, Bulukumba Regency. The research employed a qualitative descriptive approach. Data were collected through observation, interviews, documentation, and literature review. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings reveal that government supervision of rock quarry mining activities is carried out through two forms of supervision: preventive supervision and repressive supervision. Preventive supervision is implemented through the control of mining business licensing processes, ranging from the issuance of Mining Business Permit Areas to Mining Business Operation Production Permits. Meanwhile, repressive supervision is conducted through field inspections, guidance, and enforcement actions against violations occurring during mining operations. Although supervision has been implemented, several challenges remain, including limited understanding among business operators regarding licensing systems, violations of mining operational regulations, and suboptimal coordination and guidance among relevant institutions. Therefore, strengthening supervisory functions, improving socialization efforts, and enhancing inter-agency coordination are necessary to establish orderly, sustainable, and legally compliant mining governance.